HUBUNGAN POLA ASUH ORANG TUA DENGAN KECANDUAN GAME ONLINE PADA SISWA SMP - Hidayah, Rodhiatul; Safri, Safri; Indriati, Ganis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Parenting styles influenced the adolescents behavior. The aim of this reseach was to known the correlation between parenting styles and online gaming addiction on junior high school students. The research used proportionate stratified random sampling involving 238 students that were selected based on inclusion criteria by using parenting style quistionaire for adolescents and game addiction scale. Game addiction scale divided into positive and negative online gaming addiction. This research found that from 66 students who were not addicted to online games (negative) used authoritative parenting style (74,2%), students who were addicted to online games (positive) used permissive parenting style (55,9%). Data analysis was conducted by using chi-square test and the result showed p value (0,003) < alpha (0,05) which means that there was correlation between parenting styles and online gaming addiction. This research recommends parents to use authoritative parenting style to prevent from getting addicted to online games.Keywords : Junior high school students , online gaming addiction, parenting styles.